Effects of surface texturing and laminar plasma jet surface hardening on the tribological behaviors of GCr15 bearing steel. (May 2022) - Guo, Da; Zhang, Peng; Jiang, Yuanyuan; Song, Chenfei; Tan, DeQiang; Yu, Deping
Abstract: Surface texturing (ST) and laminar plasma jet (LPJ) surface hardening were applied to GCr15 bearing steel to improve its wear resistance. Ball-on-disk reciprocating tests were then conducted under dry and oil-lubricated conditions to investigate the tribological behaviors. Morphology and evolution of the frictional interfaces were analyzed by SEM images to reveal the anti-wear mechanism. Results show that LPJ surface hardening can remarkably reduce the wear of GCr15 bearing steel by increasing surface hardness and thus decreasing the actual contact. Whether ST can improve the wear of GCr15 bearing steel mainly depends on the evolutions of frictional interface and wear mechanisms, namely the competitive relationship of stress concentration with trap effect or hydrodynamic pressure effect under dry friction or oil-lubricated condition. Graphical Abstract: ga1 Highlights: Laminar plasma jet (LPJ) hardening and surface texturing (ST) are used for enhancing GCr15 bearing steel. Analysis of the evolution of frictional interface are conducted to determine the anti-wear mechanisms. A synergy of ST and LPJT can reduce the wear rate of GCr15 bearing steel by 70% in dry friction. LPJT inhibits the wear by increasing surface hardness and decreasing the actual contact. Role of ST depends on the competition of stress concentration with trap effect or hydrodynamic pressure effect.